ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð¿ÐµÑ€Ð²Ð¸Ñ‡Ð½Ð¾Ð¹ ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ñ‹ Ñ‚Ð¸Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð½Ð¾Ð²Ð¾Ñ€Ð¾Ð¶Ð´ÐµÐ½Ð½Ñ‹Ñ… Ð¿Ð¾Ñ€Ð¾ÑÑÑ‚ - Bilyavskaya, S. B.; Ustichenko, V. D.; Bozhok, G. A.; Legach, E. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
Effect of cryopreservation with the cooling rate of 1 degree/min and cryoprotective media based on dimethylsulfoxide (DMSO) solution on survival and viability indices of newborn piglets thyrocyte primary culture, represented by cell and follicular fractions was studied. The optimal concentrations of DMSO for cryopreservation of thyroid gland cells and follicles were established.